2001
DOI: 10.1002/1521-4141(200112)31:12<3422::aid-immu3422>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Persistent IgE synthesis in the nasal mucosa of hay fever patients

Abstract: The location of IgE synthesis has been a longstanding controversy, with previous evidence favoring either the mucosa or lymphoid tissue in the region of allergen entry. The evidence for IgE synthesis in mucosal tissues has always been circumstantial. We have developed a novel explant culture system, using ELISA and radioactive amino acid incorporation, to measure de novo IgE protein synthesis in the nasal mucosa of hay fever patients. Surprisingly, IgE synthesis continues between seasons in the explants from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 17 publications
4
73
0
1
Order By: Relevance
“…However, we found that while AID was expressed in season, it was also expressed in the nasal mucosa of GP-allergic subjects out of season, although not in the nasal mucosa of the nonallergic control subjects. The expression of AID in out-of-season patients may reflect the ongoing secretion of IL-4 by mast cells, which may be activated by local IgE (1). Recent studies have shown that IgE itself may crosslink Fc⑀RI on mast cells and stimulate the release of cytokines, including IL-4 (34).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, we found that while AID was expressed in season, it was also expressed in the nasal mucosa of GP-allergic subjects out of season, although not in the nasal mucosa of the nonallergic control subjects. The expression of AID in out-of-season patients may reflect the ongoing secretion of IL-4 by mast cells, which may be activated by local IgE (1). Recent studies have shown that IgE itself may crosslink Fc⑀RI on mast cells and stimulate the release of cytokines, including IL-4 (34).…”
Section: Discussionsupporting
confidence: 88%
“…The role of allergen in inducing this switch must be important in the pathogenesis of allergic rhinitis, because allergen induces the degranulation of mast cells, sensitized by the IgE Abs, and this IgE must be replaced to maintain the sensitization of the mast cells. We have shown that IgE synthesis occurs in the nasal mucosa in allergic rhinitis (1), and thus, presumably, the class-switched B cells also differentiate into the plasma cells that secrete the IgE.…”
Section: Discussionmentioning
confidence: 99%
“…In the fairly limited number of papers (19)(20)(21)(22)(23), including this one, in which human allergenspecific IgE Ab fragments have been isolated, combinatorial libraries have always been cloned from peripheral blood samples. However, an essential aspect of the evolving IgE response is the accumulating evidence that both class-switch recombination (24)(25)(26)(27) and somatic hypermutation (25) followed by clonal expansion and IgE production (28,29) occur in local airway mucosa under the influence of the inflamed tissue (reviewed in Ref. 30).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that IgE is produced in the local lymphoid tissues and locally in both the nasal and bronchial mucosa (761,762). PER IgE synthesis takes place in the nasal mucosa during and just after the pollen season (763). Allergen drives class switching to IgE in the nasal mucosa in allergic rhinitis (764).…”
Section: Allergic Inflammationmentioning
confidence: 99%